Asociación entre la participación en programas de asistencia alimentaria y patrones del perfil lipídico en Perú. - Paredes-Aramburú, Jacqueline (2018)
Purpose: To assess whether the participation in food assistance programs (Community Kitchens and Glass of Milk) was associated with lipid profile patterns in the Peruvian population. We conducted a secondary data analysis using data from the National Survey of Nutritional, Biochemical, Socioeconomic, and Cultural Indicators related to Chronic Degenerative Diseases. The sample included individuals aged ≥20 years, selected from five geographic strata in Peru. From each stratum a random sample of clusters was chosen. Different Poisson regression models with robust variance were built to determine the association between food assistance programs and participant lipid profile (total cholesterol (TC), HDL-cholesterol (HDL-c), LDL-cholesterol and triglycerides (TG)). Data from 4028 participants was analyzed, 123 (3.1%) reported being beneficiaries of the Community Kitchens program and 827 (20.5%) were beneficiaries of the Glass of Milk program. An association between being a beneficiary of Community Kitchens and increased LDL-c (Prevalence ratio (PR)= 2.33; 95% CI: 1.18–4.59) was found. Being a beneficiary of the Glass of Milk program increased the probability of having low HDL-c levels (PR= 1.08; 95% CI: 1.02–1.14), but reduced the probability of hypertriglyceridemia (PR= 0.70; 95% CI: 0.56–0.88). Being a beneficiary of the Community Kitchen program was associated with increased LDL-c levels; while, being a beneficiary of the Glass of Milk increased the probability of low HDL-c, but reduced the probability of developing hypertriglyceridemia.